2009
DOI: 10.4081/ijas.2009.s1.301
|View full text |Cite
|
Sign up to set email alerts
|

Model to evaluate welfare in dairy cow farms

Abstract: The assessment of herd welfare is a scientific discipline that is rapidly developing. The scientific community plays an important role in delivering appropriate, repeatable, valid and feasible models for this assessment. Unfortunately, there are different feelings regarding the welfare of animals and it is imperative for its assessment that certain agreement on the meaning of animal welfare is accepted. Then it is necessary to look at the goals of the models of welfare assessment because different goals requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…Input factors can often be assessed with a high degree of reliability [ 43 ], but are perhaps more suited to informing farmers about possible prevention and solution strategies to problems, rather than identifying and assessing the health and mental well-being of the animals [ 44 ]. It has been shown that resource-based parameters alone are not sufficient to assess welfare e.g., [ 45 ] and can be thought of as providing a “risk assessment” (or “housing condition assessment”) as opposed to a welfare assessment [ 46 , 47 , 48 ]. This could, however, be overcome by using resource-based parameters that have strong links with animal-based measures and can reliably predict welfare at the individual level [ 49 ].…”
Section: Models In Farm Animal Welfarementioning
confidence: 99%
See 1 more Smart Citation
“…Input factors can often be assessed with a high degree of reliability [ 43 ], but are perhaps more suited to informing farmers about possible prevention and solution strategies to problems, rather than identifying and assessing the health and mental well-being of the animals [ 44 ]. It has been shown that resource-based parameters alone are not sufficient to assess welfare e.g., [ 45 ] and can be thought of as providing a “risk assessment” (or “housing condition assessment”) as opposed to a welfare assessment [ 46 , 47 , 48 ]. This could, however, be overcome by using resource-based parameters that have strong links with animal-based measures and can reliably predict welfare at the individual level [ 49 ].…”
Section: Models In Farm Animal Welfarementioning
confidence: 99%
“…Assessment models have been developed for cattle e.g., [ 41 , 46 , 47 , 51 ], pigs e.g., [ 42 , 52 ], poultry e.g., [ 48 , 53 , 54 ], farmed mink and foxes [ 55 ], and to evaluate enrichment materials for pigs (RICHPIG e.g., [ 56 ]). Other researchers have modified existing models for use in their studies.…”
Section: Models In Farm Animal Welfarementioning
confidence: 99%
“…The higher average values of cortisol have been observed in chronically stressed herds, selected with the model proposed by Calamari and Bertoni (2009) which is suggested to objectively evaluate the welfare situation of dairy farms. This relationship was confirmed in another trial where the basal cortisol level and its increase during restraint appear to be related (Trevisi et al, 2005).…”
Section: Cortisolmentioning
confidence: 99%
“…The welfare evaluation of dairy cows has not been discussed because there is a specific companion paper on that topic (Calamari and Bertoni, 2009 …”
Section: Discussionmentioning
confidence: 99%